Baniya’s Maharani: Dismantling Maharani Myth - Upadhyay , Toya Nath (Dhaulagiri Journal of Contemporary Issues, 2024)
This paper makes a review of Chandra Prakash Baniya's Madan Puraskar winning novel, Maharani (2019). Written in local colour, the book is a historical fiction that unveils an untold history of the Parbat Rajya (one of the 24 states before the unification of modern Nepal by Prithvi Narayan Shah). The main story revolves round the rivalry of two siblings, Bhadribam and Malebam for the ascendency to the throne. Bhadribam is elder by conception whereas Malebam by birth. As per the prevailing practice, the royal court decides in favour of Malebam. Bhadribam rebels. Vishwaprabha, the princess of Deupur who is engaged with Malebam for marriage, becomes victimized in the rivalry. Despite being engaged with Malebam, she gets ready to marry Bhadribam to save the Parbat Rajya from being divided. Ambitiously, even after having Vishwaprabha, Bhadribam continues to plot against Malebam for the throne. Vishwaprabha spoils his conspiracy and saves the Parbat Rajya. In recognition of this, Malebam awards her with the title of Maharani (Queen Mother). But Vishwaprabha does not enjoy this political title. She rather chooses the life of a recluse and goes missing soon. However, after her disappearance, she remains deeply in the collective memory of the people of Beni and the neighbouring areas. In course of time, mythicizing her as goddess, they begin to worship her. But Baniya defies this myth and simply regards her as a brave and patriotic lady. This review revolves around the question: how and why does the writer dismantle the myth in the novel, Maharani?